A Narrowband Photo‐Thermoelectric Detector Using Photonic Crystal. Issue 3 (3rd December 2018) - Monshat, Hosein; Liu, Longju; Lu, Meng
Abstract: Here, a wavelength‐specific photo‐thermoelectric (PTE) device is reported that achieves narrowband optical absorption and thermoelectric conversion functions using a stack of thin films on a grating‐patterned substrate. Conventional PTE devices are broadband with the absorption of electromagnetic radiation from ultraviolet to terahertz. There are demands for PTE devices that can exhibit narrowband response at a desired wavelength. Here, the narrowband PTE device consists of a photonic crystal (PC) filter with metal cladding and a thin‐film thermocouple. The PC‐PTE design is investigated numerically to illustrate the underlying energy conversion mechanism. The device is fabricated using nanoreplica molding followed by coating of thin films. The fabricated metal‐cladding PC resonator exhibits a narrowband optical absorption with a resonant absorption coefficient of 85.4% and full‐width‐half‐maximum of 14.8 nm in the visible wavelength range. The PTE measurements show that the thermoelectric output is sensitive to the coupling of incident light and guided‐mode resonance modes. Illuminated under the resonant condition, the PTE device exhibits a responsivity and noise equivalent power of 0.26 V W −1 and 7.5 nW Hz −1/2, respectively. This PC‐PTE technology has the unique attributes of narrowband detection, large surface area, and low cost for the potential application in sensors, optical spectroscopy, and imaging. Abstract : A photo‐thermoelectric (PTE) device is demonstrated to achieve narrowband optical absorption and thermoelectric conversion . Consisting of a thin‐film stack on a photonic crystal (PC) substrate, the PC‐PTE device provides resonant absorptions with the absorption coefficient of 85.4% and full‐width‐half‐maximum of 14.8 nm in the visible range. Illuminated under resonant condition, the narrowband PC‐PTE device exhibits a responsivity of 0.26 V W −1 .